IEEE 802.11n Physical Layer Implementation on Field Programmable Gate Array - Hendra Setiawan; Yuhei Nagao; Masayuki Kurosaki; Hiroshi Ochi (Universitas Ahmad Dahlan, 2012)
Register transfer level (RTL) development is a time cost step that requires high diligence and fidelity to get the valid interpretation of abstraction function of digital circuit. In this research, we introduce and prove that Model-Based Design Process (MBDP) is an effective and efficient way to develop a RTL complex system such as wireless communication. Using MBDP flow, we interpret, develop, and verify the physical layer RTL of a new standard that ratified on the end 2009, i.e. IEEE 802.11n wireless local area network (WLAN). The result of this research is a prototyping FPGA StratixII EP2S180 that has properly worked as a 2x2 MIMO WLAN with maximum throughput 144 Mbps.